Optimal temperature management in aortic arch surgery: A systematic review and network meta‐analysis. Issue 12 (15th November 2022) - Abjigitova, Djamila; Notenboom, Maximiliaan L.; Veen, Kevin M.; van Tussenbroek, Gabriëlle; Bekkers, Jos A.; Mokhles, Mostafa M.; Bogers, Ad J. J. C.
Abstract: Objectives: New temperature management concepts of moderate and mild hypothermic circulatory arrest during aortic arch surgery have gained weight over profound cooling. Comparisons of all temperature levels have rarely been performed. We performed direct and indirect comparisons of deep hypothermic circulatory arrest (DHCA) (≤20°C), moderate hypothermic circulatory arrest (MHCA) (20.1–25°C), and mild hypothermic circulatory arrest (mild HCA) (≥25.1°C) in a network meta‐analysis. Methods: The literature was systematically searched for all papers published through February 2022 reporting on clinical outcomes after aortic arch surgery utilizing DHCA, MHCA and mild HCA. The primary outcome was operative mortality. The secondary outcomes were postoperative stroke and acute kidney failure (AKI). Results: A total of 34 studies were included, with a total of 12, 370 patients. DHCA was associated with significantly higher postoperative incidence of stroke when compared with MHCA (odds ratio [OR], 1.46, 95% confidence interval [CI], 1.19–1.78) and mild HCA: (OR, 1.50, 95% CI, 1.14–1.98). Furthermore, DHCA and MHCA were associated with higher operative mortality when compared with mild HCA (OR 1.71, 95% CI, 1.23–2.39 and OR 1.50, 95% CI, 1.12–2.00, respectively). Separate analysis of randomized and propensity score matched studies showed sustained increased risk of stroke with DHCA in contrast to MHCA and mild HCA (OR, 1.61, 95% CI, 1.18–2.20, p value = .0029 and OR, 1.74, 95% CI, 1.09–2.77, p value = .019). Conclusions: In the included studies, the moderate to mild hypothermia strategies were associated with decreased operative mortality and the risk of postoperative stroke. Large‐scale prospective studies are warranted to further explore appropriate temperature management for the treatment of aortic arch pathologies.